Efektifitas Terapi Clapping Terhadap Peningkatan Saturasi Oksigen Pada Remaja dengan Tuberculosis - Yeni Ika Wulandari; Raden Maria Veronika Trilupi; Apriyani Puji Hastuti (Universitas Pahlawan Tuanku Tambusai, 2026)
Pulmonary tuberculosis (TB) remains a global health problem and often causes respiratory disorders, including decreased oxygen saturation. This condition requires effective nursing interventions to improve respiratory function. This study aimed to determine the effectiveness of clapping therapy in increasing oxygen saturation among adolescents with pulmonary TB at Dr. Saiful Anwar Regional Hospital, Malang. This study used a quasi-experimental design with a pretest-posttest control group approach. The sample consisted of 30 respondents, divided into an intervention group and a control group, with 15 respondents each. The intervention group received clapping therapy combined with nebulizer treatment, while the control group received standard therapy using a nebulizer only. Measurements were taken before and after the intervention using a sphygmomanometer, pulse measurement, and pulse oximeter. Data were analyzed using the Wilcoxon test and independent t-test with a significance level of α = 0.05. The results showed a significant increase in oxygen saturation in the intervention group from 95.73% to 99.80% with a p-value of 0.001. Meanwhile, changes in blood pressure and pulse rate were not statistically significant. These findings indicate that clapping therapy is effective in improving oxygenation without negatively affecting hemodynamic parameters. In conclusion, clapping therapy is an effective, safe, and applicable nursing intervention to improve oxygen saturation in adolescents with pulmonary tuberculosis.